Serum levels of AFP and CA19-9 after Intraoperative Radiotherapy Combined with Drug Therapy on Liver and Pancreatic Tumors: Serum levels of AFP and CA19-9 in Liver and Pancreatic Tumors - Jia, Xin; Jiang, Zongliang (Journal of Medical Biochemistry, 2025)
Objective To explore the efficacy of intraoperative radiotherapy combined with drug therapy on serum levels of AFP and CA19-9 for liver and pancreatic tumors to provide more effective treatment strategies for clinical practice. Method A retrospective analysis was conducted on 190 patients with liver and pancreatic tumors who underwent surgical resection combined with intraoperative radiotherapy in the hospital from March 2023 to September 2024. The patients were segmented into an experimental group (intraoperative radiotherapy combined with drug therapy, n=95) and a control group (traditional treatment, n=95) at random. The experimental group accepted IORT, targeted drugs, and immunomodulators after surgical resection. The control group received surgical resection and chemotherapy or external radiation therapy. The main observation indicators include tumor marker levels, biochemical indicators, recurrence rate, survival rate, quality of life, postoperative complications, pain score, and psychological status. Results The levels of AFP and CA19-9 in the experimental group decreased by 16.2 ng/mL and 74.7 U/mL, which surpassed those in the control group (P
Keywords: AFP , CA19-9, Intraoperative radiotherapy; Medication; Tumor markers; Hepatopancreatic tumors; Recurrence rate